The Effectiveness of the Implementation of the Ease of Doing Business Policy on Investment Growth in East Java - Norma Isnawati; Andy Fefta Wijaya; Moh Said (Jurnal Penelitian, 2025)
Increasing investment is a national strategic priority to boost economic growth, job creation, and regional competitiveness. A key challenge in realizing investment lies in the complexity of licensing, especially environmental permits that require compliance with technical standards and sectoral regulations. To address this, the government implemented a risk-based business licensing policy through digital systems OSS and JOSS. This qualitative study analyzes the effectiveness of this policy in East Java, using a framework of institutional capacity and effectiveness, viewed from the perspective of collaboration among policy actors. Findings show that OSS and JOSS systems have improved licensing efficiency, accelerated Business Identification Number (NIB) issuance, and strengthened DPMPTSP’s role as the implementing institution. However, challenges remain in environmental licensing, including weak cross-sectoral coordination, limited human resources, inconsistent spatial and environmental data, and the absence of a structured collaborative mechanism involving local governments, businesses, and environmental oversight institutions. These barriers hinder optimal implementation. The study concludes that digital innovation alone is insufficient for successful policy outcomes. Effective implementation also requires regulatory consistency, institutional strengthening, and adaptive collaborative governance to respond to the complexity and dynamic nature of cross-sectoral policies, especially in environmentally sensitive areas.